On the Field Strength Dependence of Bi‐ and Triexponential Intravoxel Incoherent Motion (IVIM) Parameters in the Liver. Issue 6 (3rd April 2019) - Riexinger, Andreas Julian; Martin, Jan; Rauh, Susanne; Wetscherek, Andreas; Pistel, Mona; Kuder, Tristan Anselm; Nagel, Armin Michael; Uder, Michael; Hensel, Bernhard; Müller, Lars; Laun, Frederik Bernd
Abstract : Background: Studies on intravoxel incoherent motion (IVIM) imaging are carried out with different acquisition protocols. Purpose: To investigate the dependence of IVIM parameters on the B0 field strength when using a bi‐ or triexponential model. Study Type: Prospective. Study Population: 20 healthy volunteers (age: 19–28 years). Field Strength/Sequence: Volunteers were examined at two field strengths (1.5 and 3T). Diffusion‐weighted images of the abdomen were acquired at 24 b‐values ranging from 0.2 to 500 s/mm 2 . Assessment: ROIs were manually drawn in the liver. Data were fitted with a bi‐ and a triexponential IVIM model. The resulting parameters were compared between both field strengths. Statistical Tests: One‐way analysis of variance (ANOVA) and Kruskal–Wallis test were used to test the obtained IVIM parameters for a significant field strength dependency. Results: At b‐values below 6 s/mm 2, the triexponential model provided better agreement with the data than the biexponential model. The average tissue diffusivity was D = 1.22/1.00 μm 2 /msec at 1.5/3T. The average pseudodiffusion coefficients for the biexponential model were D * = 308/260 μm 2 /msec at 1.5/3T; and for the triexponential model D 1 * = 81.3/65.9 μm 2 /msec, D 2 * = 2453/2333 μm 2 /msec at 1.5/3T. The average perfusion fractions for the biexponential model were f = 0.286/0.303 at 1.5/3T; and for the triexponential model f 1 = 0.161/0.174 and f 2 = 0.152/0.159 at 1.5/3T. A significant B 0 dependence was only found for the biexponential pseudodiffusion coefficient (ANOVA/KW P = 0.037/0.0453) and tissue diffusivity (ANOVA/KW: P < 0.001). Data Conclusion: Our experimental results suggest that triexponential pseudodiffusion coefficients and perfusion fractions obtained at different field strengths could be compared across different studies using different B 0 . However, it is recommended to take the field strength into account when comparing tissue diffusivities or using the biexponential IVIM model. Considering published values for oxygenation‐dependent transversal relaxation times of blood, it is unlikely that the two blood compartments of the triexponential model represent venous and arterial blood. Level of Evidence: 1 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2019;50:1883–1892.